1993
DOI: 10.1021/jm00073a023
|View full text |Cite
|
Sign up to set email alerts
|

Troeger's base. An alternate synthesis and a structural analog with thromboxane A2 synthetase inhibitory activity

Abstract: The synthesis of 2,8-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base) from p-toluidine and of two Tröger's base analogs from other anilines by reaction with hexamethylenetetramine in trifluoroacetic acid is described. 2,3,6,7-Tetrahydro-9-methyl-2,6-di-p-tolyl-1H,5H-pyrimido[5,6,1-ij] quinazoline is formed as a secondary product in the reaction of p-toluidine and hexamethylenetetramine. One of the Tröger's base analogs, 2,8-bis(3'-pyridylmethyl)-6H,12H-5,11-methanodibenzo[b,f][1,5]d iazoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…It has been previously shown that reactions of aldehydes, or a limited selection of ketones, with the two cyclic disecondary amines shown in Figure 2 results in the formation of Tröger's base analogues with the methylene strap either mono-or di-substituted. [35][36][37] H N N H H 3 C In light of the substituents that are now available on the aryl rings of Tröger's base analogues, in the present work we sought to develop a general methodology for the synthesis of functionalised cyclic disecondary amines (strap-clipped Tröger's base analogues) and demonstrate their use in a general approach toward methano-strap modified compounds. Initially, the generality of the literature methodology 35 (Method A) was explored, however, with the exception of compounds 1 and 2, these reaction conditions were found to be unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that reactions of aldehydes, or a limited selection of ketones, with the two cyclic disecondary amines shown in Figure 2 results in the formation of Tröger's base analogues with the methylene strap either mono-or di-substituted. [35][36][37] H N N H H 3 C In light of the substituents that are now available on the aryl rings of Tröger's base analogues, in the present work we sought to develop a general methodology for the synthesis of functionalised cyclic disecondary amines (strap-clipped Tröger's base analogues) and demonstrate their use in a general approach toward methano-strap modified compounds. Initially, the generality of the literature methodology 35 (Method A) was explored, however, with the exception of compounds 1 and 2, these reaction conditions were found to be unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…For related literature, see: Becker et al (1993); Bhuiyan et al (2007); Eisner & Wagner (1934); Farrar (1964); Johnson et al (1993); Maffei (1928Maffei ( , 1929; Smith & Schubert (1948) ;Walther & Bamberg (1906); Ibers & Hamilton (1974); Wagner & Eisner (1937 Data collection: CAD-4 (Schagen et al, 1989); cell refinement: CAD-4; data reduction: local program; program(s) used to solve structure: SIR92 (Altomare et al, 1994); program(s) used to refine structure: RAELS (Rae, 1996); molecular graphics: ORTEPII (Johnson, 1976); software used to prepare material for publication: local programs.…”
Section: Related Literaturementioning
confidence: 99%
“…Due to these properties, the foremost applications of Tröger's base have been in the field of molecular recognition [3][4][5][6] although qualified for extensive usage in many other fields. [7][8][9][10] Since the synthesis of Tröger's base itself in 1887, more than 150 derivatives and analogues have been synthesized using various methods. The scope of this fascinating molecule could be even broader having access to a greater number of general methods for the synthesis of analogues and derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The yields are highly dependent on the aromatic substituents. [10,[18][19][20] A methodology based on first constructing the Tröger's base framework and then introducing the aryl groups as we propose in the present work, leads to greater synthetic flexibility, the tolerance to acid-sensitive groups on the aryl moiety and in general much higher yields.…”
Section: Introductionmentioning
confidence: 99%